PENGARUH LOMPATAN VERTIKAL DAN HORIZONTAL TERHADAP KEMAMPUAN SHOOTING PADA TIM SEPAK BOLA PUTRI BOTUBULOWE - Moh. Gafur Ruchban; Safri Irawan; Ucok Hasian Refiater; Hartono Hadjarati; Amanda Maryani Ali Buloto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of vertical jump and horizontal jump training on shooting ability in the Botubulowe women's soccer team and to compare the effectiveness of both training forms. This study used an experimental method with a two-group pretest-posttest design. The population in this study was 45 players, while the sample of 20 players was selected using a purposive sampling technique with an age range of 17-18 years. The sample was divided into two groups: a vertical jump training group and a horizontal training group, each consisting of 10 players. The data collection technique used a shooting ability test. Data analysis was performed using IBM SPSS Statistics through normality tests, homogeneity tests, paired sample t-tests, and independent sample t-tests. The results showed that vertical jump training significantly impacted shooting ability, with a significance value of 0.000 <0.05, and an average score increase from 11.00 to 15.40. Horizontal jump training also significantly impacted shooting ability, with a significance value of 0.000 <0.05, and an average score increase from 11.00 to 13.60. Furthermore, there was a significant difference in the effect of vertical and horizontal jump training on shooting ability, with a significance value of 0.000 <0.05. Vertical jump training proved more effective than horizontal jump training in improving the shooting ability of women's soccer players in Botubulwe.